Peningkatan Kemampuan Pra Membaca Dan Pra Menulis Melalui Collaborative Play Usia 4-5 Tahun - Mulyani, Wahyu Huda; Sufa, Feri Faila; Wahyuseptiana, Yetty Isna (Jurnal Ilmiah Dikdaya, 2024)
This research is a classroom action research given to early childhood children in group A, Pembina State Kindergarten, Tasikmadu District, Karanganyar Regency, Central Java Province. Pre-reading and writing skills are really needed when children enter elementary school, however introducing reading and writing still has pros and cons. This research aims to improve the pre-reading and pre-writing collaborative play skills of children aged 4-5 years at the Pembina Tasikmadu State Kindergarten through handmade flashcards. The subjects in this study were 16 children consisting of 12 girls and 4 boys in group A of the Pembina Tasikmadu State Kindergarten. This classroom action research was carried out in 2 research cycles. The results of the research carried out showed that the average pre-cycle score was 12.5, while in cycle 1 it was 50, and in cycle 2 it was 37.5. The results of this research showed that collaborative play handmade flashcards significantly improved children's pre-reading and pre-writing abilities. early childhood at the Pembina Tasikmadu Karanganyar State Kindergarten.